Mutant Strains of Rhodopseudomonas spheroides Lacking δ-Aminolevulinate Synthase: Growth, Heme, and Bacteriochlorophyll Synthesis - Lascelles, June (1969)
Two mutant strains of Rhodopseudomonas spheroides were described which lacked δ-aminolevulinate synthase activity. They required δ-aminolevulinate for growth; they did not respond to protoporphyrin or magnesium photoporphyrin, and only poorly to hemin. Synthesis of cytochromes and heme by mutant H-4 was dependent upon δ-aminolevulinate; this strain did not form bacteriochlorophyll either with or without δ-aminolevulinate and, consequently, grew only under aerobic conditions. Mutant H-5 formed bacteriochlorophyll in response to δ-aminolevulinate and grew both anaerobically in the light and aerobically in the dark; the amount of δ-aminolevulinate needed for optimal anaerobic growth was higher than that required aerobically. Synthesis of bacteriochlorophyll and heme by suspensions of mutant H-5 incubated anaerobically in the light was dependent upon δ-aminolevulinate; bacteriochlorophyll production was completely inhibited by high aeration and by puromycin. The mutants differed in their ability to take up radioactive δ-aminolevulinate from the external environment; mutant H-5 was less active than mutant H-4 or the wild type. It was suggested that R. spheroides made only one form of δ-aminolevulinate synthase, which provided δ-aminolevulinate for bacteriochlorophyll and heme synthesis.